The Effect of Education of Medication by Small Groups Discussion on Nursing Adherence in Intensive Care Units of Medication Standards - Gholam Hossein Falahinia; Arezoo Maleki; Zahra Khalili; Alireza Soltanian (Hamadan University of Medical Sciences, 2019)
Introduction: Adherence of standards requires the continuous of education for nurses. Effective educational methods for increasing knowledge and enhancing skills is group discussion. The purpose is to determine the effect of education of medication by small groups discussion on nursing adherence in intensive care units of medication Standards. Methods: In this semi-experimental study the intensive care units of two hospitals that were randomly assigned as intervention and control groups 76 nurses were enrolled in the census. The medication standards checklist was designed in 25 sections and 53 questions. The researcher using the checklist, controlled each nurse's adherence of the medication standards in four steps before and after the education, subtle and direct observation. If adherence score 1 and in non adherence score zero was earned. The education of medication standards was conducted in the intervention group by group discussion method during two sessions of two-hours. Data analysis was performed using SPSS 16 and independent t-test and paired t-test. Results: There was no statistically significant difference between the two groups in term of the rate of adherence of nurses from the medication standards before intervention (P>0.05). After intervention, nurses' adherence significantly increased in the intervention group (87.9±2.5) compared to the control group (77.7±2.7) (P<0.001). Conclusion: Considering the positive effects of education using group discussion method on nursing adherence of medication standards and the importance of this issue regarding the care of patients, using this method for nurses' education is suggested.